A randomized clinical study to compare implant stability and bone loss using early loading protocol in two implant systems with different design - Rani Ranabhatt; Kamleshwar Singh; Ramashanker Siddharth; Shuchi Tripathi; Deeksha Arya (Wolters Kluwer Medknow Publications, 2021)
Aims: The study compared changes in implant stability and bone loss of implants with different designs using early loading at 6 weeks. Setting and Design: In vivo-comparative study. Materials and Methods: Forty subjects were selected and divided randomly by sealed envelope method in Group X and Group A for early loading for missing single posterior tooth in mandible. Implants in Group X had flared crest module and buttress thread design, whereas implants in Group A had parallel crest module and V-shaped thread design. All subjects were evaluated by Ostell for implant stability at the interval of baseline, 6 weeks, 3 months, and 6 months. ImageJ software was used for measurement of crestal bone loss in intraoral periapical radiographs at the interval of 6 weeks, 3 months, and 6 months. Statistical Analysis Used: Unpaired t test, repeated ANOVA, Tukey post hoc test. Results: The mean bone loss values of Group X at predetermined interval were 1.51 ± 0.20 mm, 2.11 ± 0.21 mm and 2.13 ± 0.21 mm. The mean bone loss values of Group A were 1.79 ± 0.16 mm, 2.92 ± 0.23 mm and 2.95 ± 0.23 mm. The mean bone loss was statistical significant (P < 0.05) at 6 weeks, 3 months and 6 months. It was highly significant in Group A at 6 months (P < 0.001). Conclusions: It was concluded that Group X implants design showed better implant stability and less bone loss when compared to Group A implants design.